PENGARUH PAJAK HIBURAN TERHADAP PENDAPATAN ASLI DAERAH PADA MASA PANDEMI COVID-19 KOTA BANJARMASIN - Afriliani Kartika Sari; Nasrudin; Asrid Juniar (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2022)
The largest income in Indonesia is income derived from Tax Collection, one of which is the Entertainment Tax. With the tax, it is hoped that it can finance the development and welfare of the Indonesian people. However, in early 2020, precisely in March, Indonesia experienced a global crisis, namely the outbreak of Covid-19 which resulted in many developments being temporarily halted and the welfare of the people could not be handled properly. This research was conducted based on an outbreak that hit the world, namely the Covid-19 Pandemic, which aims to find out whether the Covid-19 Pandemic has a positive or negative impact on Taxes, especially in Indonesia, especially in the City of Banjarmasin.